Causal associations between fluid intake patterns and dermatitis risk: a Mendelian randomization study - Zeng, Ruiqi; Guo, Beian; Liao, Wanzhe; Zhuan, Kairui; Chen, Huilan; Qin, Zixiang; Lin, Junxi; Gu, Tingyu; Zhou, Zhiyi (Frontiers in Nutrition, 2024)
Background: Dermatitis is one of the most common skin disorders across the world. Atopic dermatitis (AD) and contact dermatitis (CD) are its two primary types. Few studies have focused on the causal relationship between fluid intake and dermatitis. With an Mendelian Randomization (MR), this study investigated the potential causal effects of alcohol, coffee, tea, and water intake on the risk of AD and CD. Methods: Utilizing genetic variants as instrumental variables (IVs), a two-sample MR analysis was implemented based on data from the UK Biobank and FinnGen r9 consortium. Fluid intake was categorized into alcohol, coffee, tea, and water intake. Causal estimates were analyzed through Inverse Variance Weighted (IVW), MR-Egger, and weighted median methods. Cochran's Q, MR-Egger intercept, and MR-PRESSO tests were conducted to assess potential heterogeneity and pleiotropy. Results: Water intake exhibited a significant causal effect on raised CD risk (IVW OR = 2.92, 95% CI: 1.58-5.41, P = ＜0.01). Coffee intake was associated with increased CD risk (IVW OR = 2.16, 95% CI: 1.19-3.91, P = 0.01). Conversely, tea intake demonstrated a protective effect on AD risk (IVW OR = 0.71, 95% CI: 0.56-0.91, P = ＜0.01).This MR study suggests a potential association where water and coffee intake may be linked to an elevated risk of CD, while tea intake may potentially have a mitigating effect on AD risk. Modifying fluid intake patterns could be a targeted approach for dermatitis prevention, emphasizing the need for additional longitudinal studies to validate and expand upon these findings.